(untitled) (مجلة البحوث الأكاديمية, 2019)
Background: Infertility is considered as one of the main health problems affecting about 10- 15% of couples seeking children. However, in 50% of these the male partner is responsible for infertility. Y chromosome classical microdeletions in the azoospermia factor (AZF) regions are known to be associated with spermatogenic failure. Spermatogenesis is an essential reproductive process that is regulated by many Y chromosome specific genes. The Y-chromosome is the smallest chromosome that consists of 2-3% of the haploid genome and may contain between 70 and 200 genes.